Avaliação nutricional de paciente com deficiência de biotinidase - RODRIGUES, Kethleen Paula Monteiro (2023)
Biotinidase deficiency is an inborn error of metabolism with an autosomal recessive pattern of inheritance, where biotinidase enzyme activity is absent or reduced as a result, the body is unable to recycle biotin and has the loss of biocytin in the urine with subsequent elimination of biocytin in the urine. It can be classified into two subgroups: profound and partial deficiency, depending on the enzymatic activity which is approximately less than 10% and between 10 and 30% of the average normal activity, respectively. Clinical manifestations include: alopecia, developmental delay, muscle hypotonia, epileptic seizures, skin infections, conjunctivitis, hearing impairment, lethargy, respiratory problems, visual impairments, coma, diarrhea and fungal infections. The diagnosis can be made by neonatal screening better known for Newborn Screening Test before the onset of symptoms, as early as possible. Treatment is through oral administration of biotin. in doses of 5 to 20 mg, regardless of weight and age. The treatment is simple and inexpensive. Objective: Evaluate the nutritional profile of a patient with biotinidase deficiency diagnosed in a reference laboratory for inborn errors of metabolism. Methodology: Data were collected from the patient's medical records and nutritional assessments were performed, weight, height, arm and waist circumference were measured, beyond triceps and subscapular skinfolds, head circumference additionally and a food frequency questionnaire was applied. Results: A diagnosis of malnutrition, mild deficit of fat mass, low weight for age, very short height for age and BMI with risk of overweight for age were obtained. Conclusion: Because it is only one patient, the results are limited and more studies related to the nutritional management of patients diagnosed with biotinidase deficiency are needed.